Increased Demodex Density and Risk of Demodicosis After Septorhinoplasty: A Prospective Cohort Study - Kulaklı, Sevgi; Oğuz, Işıl Deniz; Çoluk, Yonca (Dermatology Practical & Conceptual, 2026)
Introduction: Demodex mites reside in the hair follicles and sebaceous glands of the head and face. An increase in their population can lead to primary or secondary demodicosis. Septorhinoplasty is a frequently performed aesthetic surgical procedure that can cause various cutaneous complications in the facial area.Objectives: This study aimed to investigate the density of Demodex mites and the prevalence of demodicosis following septorhinoplasty.Methods: A total of 40 patients (29 females, 11 males) scheduled for septorhinoplasty, with a mean age of 26.25±7.47 years, were evaluated for clinical findings of demodicosis before and at the third month after surgery. Demodex density was assessed using the standardized skin surface biopsy technique, a noninvasive method involving cyanoacrylate adhesive, and microscopic evaluation of samples taken from the bilateral cheeks and nose.Results: A statistically significant increase was observed in the number of Demodex mites in the malar and nasal regions and in the prevalence of demodicosis following septorhinoplasty. Additionally, the frequency of seborrhea and pustules showed a significant rise. Symptoms related to demodicosis were found to appear around the 22nd postoperative day and persisted up to the third month.Conclusions: Demodicosis should be considered in the differential diagnosis of patients presenting with erythema, papules, and pustules in both the early and late postoperative periods following septorhinoplasty, and necessary diagnostic investigations should be performed. Further large-scale studies with a greater number of patients are required to support our findings.